EXPLORING THE BRAND ORIGIN EFFECT ON CHINESE AUTOMOBILES : A CASE STUDY OF WULING MOTORS IN MANADO - Wullur, Timothy .; Tumbuan, Willem J.F.A; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Wuling Motors is a newcomer in the Indonesian car market. The purpose of this study is to provide insight into the Wuling automobile product and effects of its brand origin. This is done by interviewing 30 consumers to provide their insight and review of the brand origin and the quality of the product itself, from the perspective of owners as well as non-owners. This research is a qualitative research using case study approach. The results show that Chinese brand origin is still a disadvantage in attracting potential buyers, because the stigma and negative stereotypes are still evident. There is still doubt regarding the product’s build quality and serviceability. Consumers perceive that Wuling’s strongest points are its features and its luxuriousness. Performance and exterior toughness are also strengths of the Wuling automobile. The weaknesses are in its firm reputation which is still unsettled, and the maintenance and repair service is still found to be lacking, both in scale and quality of service. The company is advised to grow its service capabilities in order to provide more satisfaction for the consumers, create more trust in the product and at the same time improve its reputation. Keywords: brand origin and perceived quality